5x+-6y-x+8y=

Simple and best practice solution for 5x+-6y-x+8y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+-6y-x+8y= equation:


Simplifying
5x + -6y + -1x + 8y = 0

Reorder the terms:
5x + -1x + -6y + 8y = 0

Combine like terms: 5x + -1x = 4x
4x + -6y + 8y = 0

Combine like terms: -6y + 8y = 2y
4x + 2y = 0

Solving
4x + 2y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2y' to each side of the equation.
4x + 2y + -2y = 0 + -2y

Combine like terms: 2y + -2y = 0
4x + 0 = 0 + -2y
4x = 0 + -2y
Remove the zero:
4x = -2y

Divide each side by '4'.
x = -0.5y

Simplifying
x = -0.5y

See similar equations:

| x^3+6x=27 | | 4(3-5x)=-168 | | 8+4b+b=6b-3b | | 5+c= | | 2x-5+9x=44 | | 4x-7y-2x+10y-3y= | | 2x+9x-5=44 | | 7(10-4x)=70 | | (1)ln(5)=f(1) | | -4-8b=-2(3b-1)-2 | | 4(x^3)-2x=0 | | 9x+6y-5x-11y+7y= | | k-4=12 | | 5t=-750 | | -2y+1=6y | | 2(3x-1)+3(3y-y-x)= | | 3(c-11)=12 | | -2y+0=6y | | (4x-10)(-2)= | | 140=3x+8x+8 | | 5a+7=3a+39 | | 6w-10+-18w= | | 2(30)+8= | | 4+8=36 | | 1-(1/2)(-x+5)=2+3(1-x) | | 15-4x=32 | | 7x-5(2x+2)=-19 | | -14p=156 | | 5+5y-5y=5 | | 17+x=3+17 | | -2(x-8)=6(x+4)-8 | | 5x+8-7x-12= |

Equations solver categories